2023
DOI: 10.1093/nar/gkad534
|View full text |Cite
|
Sign up to set email alerts
|

Direct m6A recognition by IMP1 underlays an alternative model of target selection for non-canonical methyl-readers

Abstract: m6A methylation provides an essential layer of regulation in organismal development, and is aberrant in a range of cancers and neuro-pathologies. The information encoded by m6A methylation is integrated into existing RNA regulatory networks by RNA binding proteins that recognise methylated sites, the m6A readers. m6A readers include a well-characterised class of dedicated proteins, the YTH proteins, as well as a broader group of multi-functional regulators where recognition of m6A is only partially understood.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
(102 reference statements)
0
5
0
Order By: Relevance
“…A recent structural study has further revealed that the hydrophobic groove within KH4 of IGF2BPs contains a dedicated and evolutionarily conserved structural element that conveys m 6 A specificity. While this m 6 A recognition is independent of the underlying RNA sequence context, there is a preference for GGAC, with double mutations of V523I/P524S shown to significantly reduce cognate binding [ 55 ]. Interaction between IGF2BPs and m 6 A is observed only at certain m 6 A sites, as revealed by cross-linking and immunoprecipitation followed by high-throughput sequencing (CLIP-seq) analysis [ 15 , 55 ], in contrast with YTH-domain-containing proteins.…”
Section: A Enhances Rna Stabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…A recent structural study has further revealed that the hydrophobic groove within KH4 of IGF2BPs contains a dedicated and evolutionarily conserved structural element that conveys m 6 A specificity. While this m 6 A recognition is independent of the underlying RNA sequence context, there is a preference for GGAC, with double mutations of V523I/P524S shown to significantly reduce cognate binding [ 55 ]. Interaction between IGF2BPs and m 6 A is observed only at certain m 6 A sites, as revealed by cross-linking and immunoprecipitation followed by high-throughput sequencing (CLIP-seq) analysis [ 15 , 55 ], in contrast with YTH-domain-containing proteins.…”
Section: A Enhances Rna Stabilitymentioning
confidence: 99%
“…While this m 6 A recognition is independent of the underlying RNA sequence context, there is a preference for GGAC, with double mutations of V523I/P524S shown to significantly reduce cognate binding [ 55 ]. Interaction between IGF2BPs and m 6 A is observed only at certain m 6 A sites, as revealed by cross-linking and immunoprecipitation followed by high-throughput sequencing (CLIP-seq) analysis [ 15 , 55 ], in contrast with YTH-domain-containing proteins. This suggests that m 6 A does not represent a universal layer of regulation in IGF2BPs target selection.…”
Section: A Enhances Rna Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…[30] Insulinlike growth factor 2 mRNA-binding proteins 1, 2, and 3 (IGF2BP1-3), and Fragile X mental retardation 1 (FMR1) bind m 6 A with high-affinity utilizing their K homolog (KH) domain, which undergoes a local structural rearrangement and creates an open hydrophobic platform to accommodate the methyl group upon binding to m 6 A. [31][32][33] m 6 A modification of mRNA has been shown to play a significant role at multiple levels of regulation to help maintain homeostasis of host organism. At molecular level, it influences the metabolism of mRNA by mediating its splicing, export, translation, and degradation.…”
Section: Introductionmentioning
confidence: 99%
“…IMP1, a recently described m 6 A reader, interacts with the modification via a dedicated hydrophobic platform, enabling a high-affinity interaction ( Table 1 ). This interaction is sequence-independent but is embedded into the methylation-independent sequence preference of IMP1, GGAC, which has significant similarity with the METTL3/METTL14 DRACH motif ( Nicastro et al, 2023 ). The methyl group within the binding sequence results only in a small change in the on-rate from k on = 1.3 × 10 5 ± 0.1 × 10 5 M −1 s −1 to k on = 8.7 × 10 4 ± 0.1 × 10 4 M −1 s −1 but a more significant decrease in the off-rate from k off = 2.7 × 10 −3 ± 0.4 × 10 −3 s −1 to k off = 3.2 × 10 −4 ± 0.7 × 10 −4 s −1 , highlighting how the modification can specifically increase the lifetime of a protein–RNA complex.…”
Section: Introductionmentioning
confidence: 99%